2018
DOI: 10.3171/2017.5.jns163045
|View full text |Cite
|
Sign up to set email alerts
|

Resection of primary motor cortex tumors: feasibility and surgical outcomes

Abstract: Resection of tumors from the primary motor cortex is associated with an increased risk of motor deficit, but most of these deficits are transient or mild and have little functional impact. Excellent extent of resection can be achieved with intraoperative stimulation mapping, suggesting that these tumors are indeed amenable to resection and should not be labeled unresectable. Injury to small perforating or en passage blood vessels was the most common cause of infarction that led to moderate or severe deficits. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
76
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(94 citation statements)
references
References 23 publications
7
76
0
6
Order By: Relevance
“…To evaluate tumor location, M1 was divided into three motor zones (zone 1, lower limb; zone 2, upper limb; and zone 3, face), as previously reported. 9 Tumor borders were defined as well defined or irregular, 1,2 using postcontrast imaging for contrast lesions, or FLAIR images for those that were nonenhancing. Outcropping of M1 was defined as present when the tumor was reaching the cortex, either on coronal and/or sagittal FLAIR images for nonenhancing lesions, or on T1-weighted postcontrast images for enhancing lesions.…”
Section: Factors Considered For Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate tumor location, M1 was divided into three motor zones (zone 1, lower limb; zone 2, upper limb; and zone 3, face), as previously reported. 9 Tumor borders were defined as well defined or irregular, 1,2 using postcontrast imaging for contrast lesions, or FLAIR images for those that were nonenhancing. Outcropping of M1 was defined as present when the tumor was reaching the cortex, either on coronal and/or sagittal FLAIR images for nonenhancing lesions, or on T1-weighted postcontrast images for enhancing lesions.…”
Section: Factors Considered For Analysismentioning
confidence: 99%
“…7,10,17,18 More recently, evidence that the assistance of a brain mapping technique applied to M1 tumors affords an excellent resection suggests that these tumors are indeed amenable to resection and should not be labeled unresectable. 3,9 Resectability and maintenance of patient integrity depend on the ability to successfully identify motor tracts during resection. 7 In this regard, the choice of the most appropriate neurophysiological protocol to perform motor mapping is critical.…”
mentioning
confidence: 99%
“…In addition, motor deficits 6 months after surgery were categorized as mild, moderate, or severe as previously reported. 11 The motor function of each patient was assessed with manual muscle testing (MMT) as previously described. 26 Mild deficits included MMT grade 4, slight weakness, and slight incoordination, which did not impact daily life.…”
Section: Intraoperative and Postoperative Evaluationmentioning
confidence: 99%
“…A recently published study reported the feasibility and surgical outcomes of 53 resections of gliomas within the motor cortex. 11 The authors describe resection with electrical stimulation mapping of cortical and subcortical motor function. Awake craniotomy was performed in 65% of cases, whereas 35% were done under general anesthesia.…”
Section: Feasibility Of Resection Of Gliomas In the Precentral Gyrusmentioning
confidence: 99%
See 1 more Smart Citation